The Pedagogical Role of ICT on Computational Thinking in Learning Mathematics: A Systematic Review of Scopus Database - Makur, Alberta Parinters; Darhim; Martadiputra, Bambang Avip Priatna (Hipotenusa: Journal of Mathematical Society, 2024)
The systematic review literature on the integration of computational thinking in learning mathematics at K-12 mathematics education showed that student-centered teaching approaches can bridge computational thinking and mathematics. However, studies on the role of ICT in improving the quality of learning and the integration of computational thinking in supporting the academic ability of K-12 students are still little reviewed in the current literature. In an effort to fill this gap, a systematic review of the pedagogical role of ICT in asssisting the improvement of students’ computational thinking in K-12 mathematics learning needs to be conducted. This study analyzed 14 studies from the Scopus database that met the inclusion requirements. The PRISMA protocol was used to assess the 14 studies reviewed. The results of this research are that several ICT tools effectively enhance students' CT in mathematics education, including augmented reality, digital gamification technology, robots, tablets, ePCR devices, online platforms for algorithm-based tasks, and problem-based programming. These studies recommend integrating these ICT tools into standard mathematics curricula, with careful design of learning activities, appropriate to students' developmental levels, and supported by adequate teacher training.